Transforming Classical Hydropower Generation for Flexibility in the Global Energy Transition: Challenges, Requirements, and Prospects - Yannick Cyiza Karekezi; Frederic Maurer; Dany Josue Tome Robles; Thomas Oyvang; Jonas Kristiansen Noland (IEEE Access)
This review article covers the multidisciplinary challenges shaping hydropower development within a broader energy transition. Classical hydropower generation facilities are moving toward flexible operations to adapt to and facilitate the integration of variable renewable energy sources (VRES). This review article explores the paradigm shift in terms of machine design considerations, power plant operation, and grid regulator implications. Machine designers, consider magnetic saturation, energy efficiency estimation, and mechanical wear and tear. This could involve, high flux densities in certain core regions, lower weighted average efficiencies, and higher machine failures owing to insulation degradation. Moreover, power plant operators must consider the effects of the flexible power production caused by VRES. In some cases, hydropower ramping ranges from 1 to 5 megawatts (MW) per second for large hydropower plants, which pose technical challenges for operators. Moreover, transmission system operators must strengthen reactive power mandates and system-bearing ancillary service markets to ensure grid stability. In certain regions, there could be longer periods with a significant reduction in physical inertia and short-circuit grid strength owing to the lower share of classical non-inverter-based generation facilities in VRES-rich power systems.